2011
DOI: 10.3177/jnsv.57.292
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Xylooligosaccharide Preserves Hepatic Iron Storage Level in Adult Female Rats Fed a Low-Iron Diet

Abstract: Summary Iron deficiency anemia (IDA) is one of the most serious forms of malnutrition. This experiment was conducted to investigate whether acidic xylooligosaccharide (U-XOS), expected to have a high iron bioavailability, was useful in the prevention of iron deficiency. Experiment 1: Nineteen female Sprague-Dawley rats (20 wk old) were fed three different diets for 28 d; a U-XOS-supplemented low-iron diet (LI-X, n ϭ 7), a low-iron diet (LI, n ϭ 6), and a control diet (C, n ϭ 6). On day 28, the LI-X and LI grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In this connection, the partial hydrolysis of synthetic soluble fibers (Kobayashi et al, 2011) was shown to increase both iron absorption and serum iron levels when these fibers were fed to rats with iron deficiency anemia. Similarly in the present study, the use of X + C showed that the hydrolysis of native fibers increased iron in vitro bioaccessibility.…”
Section: Discussionmentioning
confidence: 98%
“…In this connection, the partial hydrolysis of synthetic soluble fibers (Kobayashi et al, 2011) was shown to increase both iron absorption and serum iron levels when these fibers were fed to rats with iron deficiency anemia. Similarly in the present study, the use of X + C showed that the hydrolysis of native fibers increased iron in vitro bioaccessibility.…”
Section: Discussionmentioning
confidence: 98%
“…5 Hardwood U-XOS with an average degree of polymerization 8-10 as diet was examined in adult female rats, showing the prevention of iron deficiency anemia. 6 Hardwood U-XOS has also served as a precursor for the formation of sulfated U-XOS designated as pentosan polysulfate, providing polysaccharides with the biological properties of glycosaminoglycans. Formulations of these products have provided orally administered treatments for interstitial cystitis (painful bladder disease) in humans 7 and injections for treatments of osteoarthritis in horses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, acidic XOSs are of interest as potential pharmaceutical agents due to their immunomodulating effects, prevention of iron deficiency anemia, and protection against the development of atopic dermatitis, etc. (3,(7)(8)(9).…”
mentioning
confidence: 99%